2023
DOI: 10.1126/sciadv.adg6004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for nontraditional mcr -containing archaea contributing to biological methanogenesis in geothermal springs

Abstract: Recent discoveries of methyl-coenzyme M reductase–encoding genes ( mcr ) in uncultured archaea beyond traditional euryarchaeotal methanogens have reshaped our view of methanogenesis. However, whether any of these nontraditional archaea perform methanogenesis remains elusive. Here, we report field and microcosm experiments based on 13 C-tracer labeling and genome-resolved metagenomics and metatranscriptomics, revealing that nontraditional archaea are predominant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…4 ), which were described in detail previously 27 . Even though some members of the Archaeoglobales and Nezhaarchaeales in Tengchong and other terrestrial spring systems have recently been shown to be methanogenic 42 , 43 , the number of transcripts mapping to mcrABG in our datasets were low.
Fig.
…”
Section: Resultsmentioning
confidence: 74%
“…4 ), which were described in detail previously 27 . Even though some members of the Archaeoglobales and Nezhaarchaeales in Tengchong and other terrestrial spring systems have recently been shown to be methanogenic 42 , 43 , the number of transcripts mapping to mcrABG in our datasets were low.
Fig.
…”
Section: Resultsmentioning
confidence: 74%
“…Collectively, our results and the studies by Wang et al . and Buessecker et al ., who reported that Mcr-encoding Archaeoglobi are present (35) and transcriptionally active in hot spring mesocosms (34), demonstrate the previously overlooked role Archaeoglobi might play in the anaerobic carbon cycle of geothermal environments.…”
Section: Resultsmentioning
confidence: 95%
“…Importantly, one of these Archaeoglobales MAGs represented the only Mcr-encoding archaeon that expressed mcrABG genes in methanogenic microcosms performed without substrate addition or with the addition of 10 mM methanol at 75 °C. This indirectly demonstrated the methanogenic nature of this archaeon (34). Last, Buessecker et al reported the establishment of a methanogenic enrichment culture of Ca.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Wang et al . reported that mcrABG and other methanogenesis marker genes encoded by two Archaeoglobales MAGs were highly expressed in hot spring microcosms incubated at 65°C and 75°C [ 34 ]. Importantly, one of these Archaeoglobales MAGs represented the only Mcr-encoding archaeon that expressed mcrABG genes in methanogenic microcosms performed without substrate addition or with the addition of 10 mM methanol at 75°C.…”
Section: Introductionmentioning
confidence: 99%